Serum Beta-2 Microglobulin as Biomarker in Chronic Lymphocytic Leukemia - Nora M. Mahgoub; Awad-Elkareem Abass; Nidal H. AL Sheikh; Esra B. AL Sheikh; Ezeldine K Abdalhabib (International Journal of Biomedicine)
Background: Beta-2 microglobulin (B2M) has been identified for many years as a reliable prognostic marker in patients with chronic lymphocytic leukemia (CLL). Our study aimed to determine the serum level of B2M in Sudanese CLL patients and correlate it with other clinical and hematological parameters. Methods and Results: A cross-sectional study was conducted at the Radio Isotopes Centre of Khartoum in Sudan. Forty-six patients previously diagnosed with CLL were enrolled in the study, and 14 healthy individuals were also included to control the assessment of B2M. Out of the 46 CLL patients (30 men and 16 women), 32 patients underwent chemotherapy treatment, while 14 patients were untreated and newly diagnosed. Complete blood count was measured using Sysmex KX-21N-TOA. The serum B2M level was measured using solid-phase sandwich ELISA. The absolute lymphocyte count was 31.3±26.8 (×109/L), with lymphocytosis in 93.8%. The mean platelet count was 158.5±66.4 (×109/L), and thrombocytopenia was noticed in 25% of the patients. The serum level of B2M was significantly higher in CLL than in healthy normal controls (7.9±6.1 mg/L versus 0.6±0.3 mg/L, P=0.000). In CLL-untreated patients, the B2M level was also significantly higher than in treated patients: 18.1±5.2 mg/L versus 5.5±3.0 mg/L (P<0.0001). The B2M level was significantly higher in patients at stages III and IV than in stages I and II: 8.6.1±5.1 mg/L versus 2.7±0.3 mg/L (P<0.0001). Conclusion: Serum B2M level correlates with the disease stages in CLL patients, and its determination could be useful in following up on CLL patients during the treatment or remission.